Enhancing Literacy and Numeracy Through Traditional Music-Based Learning in the 7th Batch of the Program Kampus Mengajar at UPTD SD Inpres Beiposo, Nusa Tenggara Timur, Indonesia - Pulu, Febryanto Blasius Keka; Fikri, Kanzul; Bupu, Hermania; Dopo, Ferdinandus Bate (SAINTIS Publishing, 2024)
Kampus Mengajar (Campus Teaching program) is one of the Merdeka Belajar Kampus Mandiri (Freedom of Learning Independent Campus) programs that aims to help improve literacy, numeracy, technology adaptation, and school administration. The main objective of the Kampus Mengajar is to prepare students with various skills and expertise through collaboration with teachers to develop innovative, creative, and interesting learning methods, while providing a positive impact on the teaching and learning process. The presence of this program provides an opportunity for students throughout Indonesia to improve their soft skills and hard skills. The purpose of the study was to find out about improving numeracy literacy through traditional music-based music art learning in the Kampus Mengajar batch 7 at UPTD SDI Beiposo, the obstacles faced and efforts to improve Literacy and Numeracy through traditional music-based music art learning in the Kampus Mengajar batch 7 at UPTD SDI Beiposo. This study uses a qualitative approach with data collection techniques using observation, interview and documentation techniques. Based on the data that has been taken, it shows that increasing numeracy literacy through traditional music-based music art learning in the 7th batch of the Kampus Mengajar at UPTD SDI Beiposo is in the form of creating a literacy and cultural festival program, creating songs for learning interests and memorizing multiplication, practicing traditional songs and music and reactivating extracurricular arts activities. The evaluation results show an increase in the average score of students in the Asesmen Kompetensi Minimum/AKM (Minimum Competency Assessment) Literacy and Numeracy post-test. This program has positive implications for increasing literacy and numeracy at UPTD SDI Beiposo. Teacher involvement, innovative, creative learning methods through traditional music-based music art learning, and support from parents are supporting factors for the success of the program.